Examining the moderating effect of self-regulation on mobile-assisted vocabulary learning outcomes among Thai EFL university students - Liu , Zhendong (Journal of Education and e-Learning Research, 2026)
The popularity of mobile technology has significantly impacted language education, especially in vocabulary acquisition. However, MAVL outcomes vary considerably, suggesting that access alone is insufficient. The present study contends that, as an essential skill in technology usage, metacognitive self-regulation acts as a crucial moderator. Quantitative in nature, the study collected data from 223 Thai university EFL students and used structural equation modeling for analysis. The study found that MAVL significantly predicted vocabulary acquisition. More importantly, it identified a significant moderator effect of self-regulation, whereby the positive correlation between MAVL and learning outcomes was notably stronger among learners high in self-regulation than those low in self-regulation, implying synergy. The study contributes to existing knowledge in several ways. First, it provides empirical evidence of self-regulation as an essential moderator in Mobile-Assisted Language Learning, shifting focus from technology-centric models to more holistic models of technology use. The study emphasizes the importance of moving beyond access to mobile technology and instead cultivating self-regulation skills in learners to bridge the “strategic divide” and reach maximum potential.